Actitudes frente a las relaciones familiares a partir del distanciamiento familiar en el personal de la estación de policía del municipio de Colón-Putumayo. (2020)
This investigation, describes the attitudes of the uniformed personnel belong to Colón Police Station located in the department of Putumayo, based on the recognition of “family estrangement phenomenon”, which is generated by the fulfillment of their ocupational liabilities. This description is made with a qualitative paradigm, using a historical hermeneutic approach, that is, the evaluation of the own personal experiences, using the technique of the interview. The discussion includes identification, recognition and determination of the components of attitudes, in their cognitive, conative or behavioural and affective spheres. The result transcends in importance, in as much as it allows to evidence the perspective from police personnel, the consequences of the " workplace transfer", in the personal sphere and of being in relation with their families.